The initiation to the professional practice of the future teacher: Articulation space between theory and reflective-investigative observation - Antunes Rodrigues, Florbela; Roque Ferreira, Maria Eduarda (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Articulating theory and critical-reflective observation of pedagogical practice, seeking to bring students closer to the research-action methodology, constitutes a central axis of the training of future teachers and the subject of Initiation to Professional Practice (IPP) assumes that dimension. This study aims to identify it in IPP reports. The analysis data is from 2017-2021 and contemplates the observation of the non-formal context in primary education. Discursive textual analysis was the methodology used to analyze the selected reports. The results indicate problems in the appropriation of reflexive questioning and the construction of argumentation.